Exploring countermovement jump variables across competitive levels and playing positions in futsal - Konstantinos Spyrou; Konstantinos Spyrou; Konstantinos Spyrou; Pedro E. Alcaraz; Pedro E. Alcaraz; Pedro E. Alcaraz; Antonio Martínez-Serrano; Antonio Martínez-Serrano; Antonio Martínez-Serrano; Elena Marín-Cascales; Elena Marín-Cascales; Elena Marín-Cascales; et al. (Frontiers Media S.A., 2024)
IntroductionThe aims of this study were to compare several countermovement jump (CMJ) kinetic variables between professional (PRO) and semi-professional (SEMI-PRO) futsal players and examine the differences amongst playing positions.MethodsCMJ performance from 56 male futsal players (25.2 ± 4.8 years; weight: 74.4 ± 6.4 kg) was analysed. Players were separated into PRO (n = 29; 27.0 ± 4.4 years; 75.4 ± 6.0 kg) and SEMI-PRO (n = 27; 22.7 ± 4.3 years; 73.1 ± 6.8 kg), and according to playing position: defenders (n = 16; 25.4 ± 3.7 years; 75.2 ± 6.0 kg), wingers (n = 26; 23.5 ± 4.5 years; 72.0 ± 6.9 kg), and pivots (n = 14; 28.0 ± 5.6 years; 77.8 ± 4.3 kg). Linear mixed models and effect sizes were used for the analyses based on the mean of two jumps for each variable.ResultsPRO players presented a deeper center of mass (COM) displacement (p = 0.002, ES = 0.83), greater eccentric (Ecc) absolute (p = 0.019, ES = 0.61) and relative peak power (p = 0.046, ES = 0.52), and achieved greater Ecc peak velocities (p = 0.004, ES = 0.76) when compared to SEMI-PRO. Non-significant and trivial-to-small differences were observed in all the other CMJ variables according to the competitive level and playing position.DiscussionEcc capabilities (i.e., deeper COM displacement, greater Ecc absolute and relative peak power, and peak velocity) during vertical jump seem to differentiate PRO and SEMI-PRO players. However, CMJ variables do not discriminate amongst playing positions in futsal players.